Outcome of patients with different clinical presentations of high-risk pulmonary embolism. Issue 7 (14th June 2021) - Ebner, Matthias; Sentler, Carmen; Harjola, Veli-Pekka; Bueno, Héctor; Lerchbaumer, Markus H; Hasenfuß, Gerd; Eckardt, Kai-Uwe; Konstantinides, Stavros V; Lankeit, Mareike
Abstract: Aims: The 2019 European Society of Cardiology (ESC) guidelines provide a revised definition of high-risk pulmonary embolism (PE) encompassing three clinical presentations: Cardiac arrest, obstructive shock, and persistent hypotension. This study investigated the prognostic implications of this new definition. Methods and results: Data from 784 consecutive PE patients prospectively enrolled in a single-centre registry were analysed. Study outcomes include an in-hospital adverse outcome (PE-related death or cardiopulmonary resuscitation) and in-hospital all-cause mortality. Overall, 86 patients (11.0%) presented with high-risk PE and more often had an adverse outcome (43.0%) compared to intermediate-high-risk patients (6.1%; P < 0.001). Patients with cardiac arrest had the highest rate of an in-hospital adverse outcome (78.4%) and mortality (59.5%; both P < 0.001 compared to intermediate-high-risk patients). Obstructive shock and persistent hypotension had similar rates of adverse outcomes (15.8% and 18.2%, respectively; P = 0.46), but the only obstructive shock was associated with an increased all-cause mortality risk. Use of an optimised venous lactate cut-off value (3.8 mmol/L) to diagnose obstructive shock allowed differentiation of adverse outcome risk between patients with shock (21.4%) and persistent hypotension (9.5%), resulting in a net reclassification improvement (0.24 ± 0.08; P = 0.002). Conclusion: The revised ESC 2019 guidelines definition of high-risk PE stratifies subgroups at different risk of in-hospital adverse outcomes and all-cause mortality. Risk prediction can be improved by using an optimised venous lactate cut-off value to diagnose obstructive shock, which might help to better assess the risk-to-benefit ratio of systemic thrombolysis in different subgroups of high-risk patients. Graphical Abstract: